SAE Technical Paper Series 2008
DOI: 10.4271/2008-22-0001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Traumatic Brain Injuries Using the Next Generation of Simulated Injury Monitor (SIMon) Finite Element Head Model

Abstract: The objective of this study was to investigate potential for traumatic brain injuries (TBI) using a newly developed, geometrically detailed, finite element head model (FEHM) within the concept of a simulated injury monitor (SIMon). The new FEHM is comprised of several parts: cerebrum, cerebellum, falx, tentorium, combined pia-arachnoid complex (PAC) with cerebro-spinal fluid (CSF), ventricles, brainstem, and parasagittal blood vessels. The model's topology was derived from human computer tomography (CT) scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
278
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(296 citation statements)
references
References 46 publications
17
278
1
Order By: Relevance
“…On the contrary, Takhounts et al 31 reported that the maximum angular velocity was correlated with CSDM 25% predicted by their SIMon brain FE model in their linear regression analyses using the same 6DOF device data used in this study. Then they proposed another brain injury criterion based on head rotational kinematics called BRIC.…”
Section: Injury Criteria Of Rotational Head Kinematicsmentioning
confidence: 80%
“…On the contrary, Takhounts et al 31 reported that the maximum angular velocity was correlated with CSDM 25% predicted by their SIMon brain FE model in their linear regression analyses using the same 6DOF device data used in this study. Then they proposed another brain injury criterion based on head rotational kinematics called BRIC.…”
Section: Injury Criteria Of Rotational Head Kinematicsmentioning
confidence: 80%
“…32,33 Finite element models will likely be an important factor in understanding this relationship. 45 Once a better understanding of these relationships is gathered, more complex methods can be used to predict brain injury in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Partially due to a lack of these properties, many assumptions have been made to model the skull/brain junction. These simplifications include: direct connection/ coupling without slipping (Ruan et al, 1991;Zhou et al, 1994;Turquier et al, 1996;Zhang et al, 2001;Kleiven and Hardy, 2002;Takhounts et al, 2008), sliding interface with different values for the coefficient of friction or tie-break thresholds (Bandak and Eppinger, 1994;Claessens et al, 1997;Miller et al, 1998), and a layer of low-shear modulus solid and frictional sliding contact (Al-Bsharat et al, 1999). Table 1 summarizes the material properties assigned to the CSF layer (PAC and CSF) in the previous modeling studies.…”
Section: Introductionmentioning
confidence: 99%
“…In most brain models, CSF layer has been modeled as incompressible, elastic material with a low shear modulus to simulate the fluid and trabeculae in the subarachnoid space. In a recent study by Takhounts et al (2008), a linear viscoelastic model simulated the CSF layer was used to allow for rate effects. Due to the lack of data to accurately characterize the biomechanical response of PAC, it is hard to determine with confidence which method best represents the in vivo situation.…”
Section: Introductionmentioning
confidence: 99%